Fabricação e caracterização de espuma de gesso para aplicações térmicas e acústicas - Arroyo, Felipe Nascimento (Universidade Federal de São Carlos, 2017)
Due to existence in abundance in Brazil, low energy consumption, less fuel quantity in its production process, not being flammable and recycling possibility, gypsum is extremely viable in civil construction. Among its applications, it is used as acoustic and thermal insulation due to the natural porosity of this material. One way to improve these applications is by adding pores. However, with pores addition in this material, its mechanical resistance decays significantly, necessitating the addition of micro silica. In this way, the study of gypsum foams for acoustic and thermal insulation together with micro silica percentages, to increase mechanical resistance, are presented as important and original from a technical and scientific point of view. The present study covered two important steps: preliminary experimental planning and definitive experimental planning. The preliminary experimental planning was important to define the base additive percentages, as well as the best water/gypsum ratio to be used and the ideal cure time. In the definitive experimental planning, the micro silica percentages were varied and statistical analysis (regression models) was performed, thus defining the best percentage of micro silica in order to reach the best result of each property. The gypsum foams results were satisfactory, reaching 87.88% porosity and excellent acoustic and thermal absorption. The micro silica also showed its effectiveness, improving 200% the uniaxial compression resistance and maintaining the effectiveness in acoustic absorption and thermal conductivity. The regression models used had representativity, in other words, with micro silica percentage, it was possible to estimate gypsum foam properties, allowing to extrapolate micro silica percentage to values not used in this research.
Gypsum foam production and characterization for thermal and acoustic applications
Producción y caracterización de espuma de yeso para aplicaciones térmicas y acústicas
Keywords: Espuma de gesso; Propriedades térmicas; Propriedades acústicas; Propriedades mecânicas; Modelos de regressão; Plaster foaming; Thermal properties; Acoustic properties; Mechanical properties; Regression models; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS